Individual and environmental determinants associated with longer times to access pediatric rheumatology centers for patients with juvenile idiopathic arthritis, a JIR cohort study - Aurélie Chausset; Céline Lambert; Alexandre Belot; Etienne Merlin; Elvira Cannizzaro; Isabelle Kone-Paut; Claire Ballot; Valérie Devauchelle; Sylvaine Poignant; Raffaella Carlomagno; Anne Lohse; Catherine Barbier; et al. (BMC, 2023)
Abstract Background Despite guidelines, poor access to appropriate care for juvenile idiopathic arthritis (JIA) patients remains a global issue. Prompt referral to a pediatric rheumatology (PR) center and effective care is known to be critical for changing the natural history of the disease and improving long-term prognosis. This project assesses socio-economic factors of delayed referral to a pediatric rheumatologist (PRst) for JIA patients in France and Switzerland within the Juvenile Inflammatory Rheumatism (JIR) Cohort. Methods All patients diagnosed with JIA, presenting at one center of the JIRcohort in France or Switzerland with additional data on referral pathway were included. Patient characteristics at first visit to the PR center, dates of visits to healthcare providers during referral, and parent characteristics were extracted from the JIRcohort database. Results Two hundred fifty children were included. The overall median time to first PR assessment was 2.4 months [1.3; 6.9] and ranged widely across the JIA subtypes, from 1.4 months [0.6; 3.8] for children with systemic juvenile idiopathic arthritis (sJIA) to 5.3 months [2.0; 19.1] for children with enthesitis-related arthritis (ERA). A diagnosis of ERA and an appointment with an orthopedist during the referral pathway were significantly associated with a longer time before the first PR visit (hazard ratio HR 0.50 [95% CI: 0.29; 0.84]) and HR 0.68 [95% CI: 0.49; 0.93], respectively) in multivariable analysis. Having a mother with a post-graduate educational attainment level was tendentially associated with a shorter time before the first PR visit, (HR 1.32 [95% CI: 0.99; 1.78]). Conclusions Time to first PRst visit was most often short compared to other studies and close to the British recommendations. However, this time remained too long for many patients. We observed no social inequities in access to a PRst, but we show the need to improve effective pathway and access to a PR center for JIA patients.